Stakeholder Collaboration On Conservation Of Natural Resources In Lower Kinabatangan Sabah - Pimid, Marcela (2018)
A failure to achieve a sustainable development of ecotourism and conservation is often related to the failure in addressing varying needs and interests of various stakeholders. Moreover, the strategies use to solve the issues of conservation and ecotourism often excludes the opinions of local communities in rural areas. The present study investigated the stakeholder collaboration in both sectors, factors and issues which influenced stakeholder collaboration on conservation and ecotourism, as well as the impacts of climate change on stakeholders, ecotourism and conservation in the Lower Kinabatangan Sabah. The aims were achieved by conducting a concurrent mixed method research using quantitative and qualitative approaches. The quantitative method gathered 328 questionnaires from each household of local communities in Sukau and Batu Puteh villages in the Lower Kinabatangan, whereas the qualitative method was conducted using a participant observation and in-depth semi-structured interviews to community leaders, local authorities, non-governmental organisations, private sectors, local and private sector ecotourism. The study highlighted five important findings. First, the number of local communities participated in conservation activities were higher compared to the ecotourism venture. Second, the surveys revealed that the local communities did not know how to participate in both activities of conservation and ecotourism, but the interview analysis showed that profit was the main factor that determined the community involvement in both sector.